URBAN AGRICULTURE AS THE PATH TO SUSTAINABLE CITY DEVELOPMENT. INSIGHTS INTO ALLOTMENT GARDENS IN ANDALUSIA - Maćkiewicz, Barbara; Puente Asuero, Raúl; Garrido Almonacid, Antonio (Quaestiones Geographicae, 2019)
Increasing demand for urban agriculture (UA) can be perceived as a global phenomenon. In some parts of the world its main function is to feed the rapidly growing population while in others it is more associated with lifestyle and environmental issues. Undeniably, UA provides opportunities for sustainable city development. UA can support all pillars of sustainable development: ecological, economic, and social. However, depending on existing circumstances certain pillars may be influenced more than others. In this paper we concentrate on urban allotments in Andalusia and take Baeza as an example of a city with an interesting approach to urban gardening. We attempt to answer the question how urban allotments in Baeza affect the city’s sustainable development and what remains to be done to make this influence more effective. Our study showed that allotment gardens in Baeza endorsed all three pillars of sustainable city development. However, developing broader community relations on the city scale, revival of declining local grocery market and dissemination of environmental initiatives which allotment gardens may also promote and facilitate was missing.